2002
DOI: 10.1192/bjp.181.6.499
|View full text |Cite
|
Sign up to set email alerts
|

Post-partum depression in a cohort of women from a rural area of Tamil Nadu, India

Abstract: Depression occurred as frequently during late pregnancy and after delivery as in developed countries, but there were cultural differences in risk factors. These findings have implications for policies regarding maternal and childcare programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

40
271
7
18

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(353 citation statements)
references
References 18 publications
40
271
7
18
Order By: Relevance
“…These risk factors are likely to be interactive as well as multiplicative in effect. These findings are consistent with findings of previous studies such as poverty, [9] low level of education [14], more than one girl child [11], pressure and desire for a male child, high adverse life events score [8], previous psychiatric disorder [15], poor spousal relation [16], and poor support from the family [8] have been implicated as risk factors, although few studies have denied one or more of these factors as significant factors [17]. The study conducted in Chennai also indicated that PPD was significantly more in women who had unskilled husbands and had nonarranged marriages.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These risk factors are likely to be interactive as well as multiplicative in effect. These findings are consistent with findings of previous studies such as poverty, [9] low level of education [14], more than one girl child [11], pressure and desire for a male child, high adverse life events score [8], previous psychiatric disorder [15], poor spousal relation [16], and poor support from the family [8] have been implicated as risk factors, although few studies have denied one or more of these factors as significant factors [17]. The study conducted in Chennai also indicated that PPD was significantly more in women who had unskilled husbands and had nonarranged marriages.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of PPD in the women attending postnatal clinic was 15.8 % in the study sample consistent with rates found in other studies with little variation in the South Asian region [8][9][10][11][12]. The study, thus, strengthens the findings of previous studies and signifies the importance of identifying PPD, more so because none of these mothers had sought help for these symptoms, although they were functionally impaired.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A series of cohort studies from developing countries have confirmed this finding 5,8,22,32,33,34 ; and a systematic review of relevant studies found that 41.5% of postnatal depression cases had arisen during the antenatal period, suggesting that interventions for depression may need to begin before childbirth 31 .…”
Section: Introductionmentioning
confidence: 92%
“…A DPP pode durar meses, apresentando sintomas intensos que acabam impossibilitando as tarefas diárias atribuídas à mãe nesse período. A maioria dos estudos refere que a DPP atinge de 10 a 15% das mulheres [3][4][5] . Entretanto, no Brasil, algumas das prevalências encontradas foram 13,4% em Brasília 6 , 37,1% em São Paulo 7 e 19,1% em Pelotas 8 .…”
Section: Introductionunclassified